The Impact of Medical Tourism on Thai Private Hospital Management: Informing Hospital Policy - James, Paul TJ (Glob J Health Sci, 2012)
BACKGROUND: The purpose of this paper is to help consolidate and understand management perceptions and experiences of a targeted group (n=7) of Vice-Presidents of international Private Thai hospitals in Bangkok regarding medical tourism impacts. METHODS: The method adopted uses a small-scale qualitative inquiry. Examines the on-going development and service management factors which contribute to the establishment and strengthening of relationships between international patients and hospital medical services provision. Develops a qualitative model that attempts to conceptualise the findings from a diverse range of management views into a framework of main (8) - Hospital Management; Hospital Processes; Hospital Technology; Quality Related; Communications; Personnel; Financial; and Patients; and consequent sub-themes (22). RESULTS: Outcomes from small-scale qualitative inquiries cannot by design be taken outside of its topical arena. This inevitably indicates that more research of this kind needs to be carried out to understand this field more effectively. The evidence suggests that Private Thai hospital management have established views about what constitutes the impact of medical tourism on hospital policies and practices when hospital staff interact with international patients. CONCLUSIONS: As the private health service sector in Thailand continues to grow, future research is needed to help hospitals provide appropriate service patterns and appropriate medical products/services that meet international patient needs and aspirations. Highlights the increasing importance of the international consumer in Thailand’s health industry. This study provides insights of private health service providers in Bangkok by helping to understand more effectively health service quality environments, subsequent service provision, and the integrated development and impacts of new medical technology.